Religious and Economic Contributions of Sayyid Hadhrami in Palembang During the 18th – 21st Centuries - Syukri, Ahmad; Mohammad Nabil Almunawar (Center for Research and Development of Religious Literature and Heritage, 2024)
As the oldest cosmopolitan city in Indonesia, Palembang has a diverse range of ethnic groups that interact on political, economic, and religious levels. Among these groups, the Sayyid Hadhrami community, descendants of the Prophet Muhammad who came from Hadramawt, South Yemen, actively preached Islam and engaged in trade in Palembang from the mid-18th century. While numerous studies have explored the Sayyid Hadrami's activities on the island of Java, few have focused on their role in Palembang. This article examines the political, economic, and religious of Sayyid Hadhrami in Palembang from the 18th to the 21st centuries. The study employs qualitative research using a historical approach. This study found that during the 18th – 19th centuries, the Sayyid Hadhrami served as clerics for Palembang propagators of Islam and intermediaries of Indian Ocean trade. Following the collapse of the Palembang sultanate in the 20th - 21st centuries, the Hadhrami community established their own religious regime. Central to their identity is their role in propagating Islam and their affiliation with the Tarekat Alawiyah, a Sufi Order originating from the Hadhrami Sayyids. Religious traditions in the Tarekat Alawiyah include Ziarah, Mawlid, and Haul. The Sayyid Hadhrami in Palembang Sucessfully transformed trade capital into religious capital to maintain their religious authority.